People’s knowledge, attitudes, and conflicts with carnivores in central hills, Sri Lanka - Ashan Thudugala; Hem Bahadur Katuwal; Nalindra Laxman; Vishwa Dushmantha; Ravindi Menikrama; Harsha Dissanayake; Chameera Dilshan; Ru-Chuan He; Rui-Chang Quan (Global Ecology and Conservation)
People’s knowledge and attitudes toward carnivores are crucial for understanding the distribution, ecology, conflicts, interactions, and threats that these species face. Carnivores are found both within and outside protected areas, making them susceptible to human-carnivore conflicts. However, In Sri Lanka, human dimensions of carnivores remain relatively understudied, despite several reported conflicts. To address these gaps, we conducted semi-structured interviews with 303 households around Dhunumadalwa Forest Reserve, Kandy, Central Sri Lanka in 2023. Our goal was to explore people's knowledge—specifically their ability to identify carnivore species and understand environmental laws—alongside their attitudes and experiences with human-carnivore conflicts. We found that 99 % of the respondents identified at least one of the 12 carnivore species shown during the interview. However, only 2 % of respondents identified as many as nine species, indicating a generally low ability to identify carnivore species. The ability to identify carnivores was significantly influenced by distance to the forest, gender, and education level. Respondents demonstrated a strong understanding of environmental laws, including forest and wildlife regulations and the penalties associated with killing species. Forty-one percent of the respondents expressed a positive attitude toward one of the carnivores, particularly leopards and other cat species, while 74 % particularly showed a negative attitude toward the civet species. The attitude towards carnivores was significantly influenced only by urbanization and education level. Carnivore conflicts were reported by 33 % of respondents, primarily involving leopards and civets, causing disturbances and economic losses. Despite these challenges, 68 % of respondents believed conflicts had decreased over the last two decades. However, 73 % of respondents had no clear idea about conflict mitigation measures, while 17 % advocated relocating problematic animals as a primary solution for conflicts. Our study highlights the complex nature of human-carnivore interactions and emphasizes the need for educating people about carnivores. It also underscores the importance of improving protection measures for domestic animals and establishing compensation schemes and performance payments to enhance tolerance, coexistence, and foster positive attitudes toward these species.